Teaching higher education staff to understand and support autistic students: evaluation of a novel training program - Jenks, Emma; Selman, Freya; Harmens, Miriam; Boon, Sarah; Tran, Trang; Hobson, Hannah; Eagle, Sarah; Sedgewick, Felicity (Frontiers in Psychiatry, 2023)
Background: Autistic students are particularly vulnerable to stressors within a university environment and are more likely to experience poor mental health than their non-autistic peers. Students' experiences of stigma from staff and peers, and the masking behaviours they deploy to minimise it, can also result in worsening mental health. Despite these concerns, there is a lack of tailored support for autistic students at university. The current project assesses a co-created training course for university staff focused on debunking stereotypes, educating about the autistic experience at university, mental health presentation among autistic individuals, and practical strategies to improve interactions with autistic students.Methods: The Autism Stigma and Knowledge Questionnaire (ASK-Q; Harrison et al., 2017) was administered before and after the training, to examine changes in trainees' understanding and acceptance of autism and autistic people. Post-training interviews and surveys were also conducted with trainees, covering the impact the training has had on their perceptions of autism, the strategies they found beneficial, and how they will use the materials in future.Results: There were no statistically significant differences between pre-and post-training scores on the ASK-Q, likely due to ceiling effects as pre-training scores were high. Thematic analysis of interviews identified five themes: value of lived experience; developing nuanced, in-depth knowledge of autism; training as acceptable and feasible; links to professional practice; and systemic barriers.Conclusions: Although ceiling effects meant there were no changes to participant's knowledge about autism and autistic people statistically, the qualitative data reveals the extensive benefits they gained from taking part in the training programmes. Scoring highly on the ASK-Q did not mean that people could not learn important new information and benefit from the course. This more nuanced understanding of autism led to practical changes in their practice. Listening to and learning from autistic people was seen as particularly important, highlighting the value of co-production. Our results also emphasise the need for varied approaches to evaluating training effectiveness, as reliance on quantitative data alone would have missed the subtler, but impactful, changes our participants experienced. This has